Understanding Older People Perceptions About Desserts Using Word Association and Sorting Task Methodologies - Arancibia-Aguilar, C; Riquelme-Hinojosa, N (Elsevier Ltd, 2022)
Techniques derived from psychology and consumer research have gained interest in the food science area to study consumers opinions and perceptions concerning food products. For that reason, Word Association (WA) and Sorting Task (ST) methods were applied to study older people s perceptions about desserts. In the WA study, older people (>60 years old) were asked about the first four words that come to mind using the following stimuli: dessert, healthy, ideal, indulgent, and ideal dessert. For ST, they had to classify 15 dessert photographs into four groups related to “healthiness” and “hedonic perception” categories. WA and ST data were analyzed by correspondence analysis and multiple correspondence analysis, respectively. Regarding WA, older people 187 terms distributed in 11 main categories: sensory characteristics, fruits, diet-health related terms, dairy products, other desserts, among others. The perceptual map showed that the different stimuli were related to emotions, healthy characteristics, hedonic characteristics, and traditional products. In the ST methodology, older people classified desserts mainly by their composition. Fruits, jelly, and yogurts were grouped in the healthy category, while the products with high sugar and fat content, such as cake, ice cream, lemon pie, were grouped in the unhealthy category. In conclusion, it is possible to know older people s opinions about desserts using WA and ST methodologies, where fruits and dairy-based desserts are considered healthy and appetizing alternatives. © 2021 Elsevier Ltd